2022
DOI: 10.1140/epjc/s10052-022-10704-3
|View full text |Cite
|
Sign up to set email alerts
|

Decaying universes and the emergence of Bell-type interuniversal entanglement in varying fundamental constants cosmological model

Abstract: In this paper, we consider a high-curvature limit of the varying fundamental constants toy model in which both the value of the speed of light and the value of the gravitational constant are related to the values of the two non-minimally coupled scalar fields. The high-curvature limit motivates the application of the third quantization procedure to such a toy model which results in a theory that describes bosonic massive particles that move freely in the three-dimensional minisuperspace associated with the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In such a model, both the speed of light and the gravitational constant are additional dynamic degrees of freedom represented by the two scalar fields with appropriate kinetic terms in the action. It was shown that such model includes a scenario in which the Universe is created in the process which is an analog of quantum scattering on the potential barrier [21] (this is similar to what was found in [22]), that the third quantization of the model leads to a scenario of the emergence of the multiverse from nothing [23], and that the created pairs of universes are entangled which is reflected by non-vanishing entanglement entropy [24,25]. Third quantization of slightly different models, in which the fundamental constants undergo cyclic evolution [26], yields insight into the relationship between quantum entanglement and thermodynamics [27].…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…In such a model, both the speed of light and the gravitational constant are additional dynamic degrees of freedom represented by the two scalar fields with appropriate kinetic terms in the action. It was shown that such model includes a scenario in which the Universe is created in the process which is an analog of quantum scattering on the potential barrier [21] (this is similar to what was found in [22]), that the third quantization of the model leads to a scenario of the emergence of the multiverse from nothing [23], and that the created pairs of universes are entangled which is reflected by non-vanishing entanglement entropy [24,25]. Third quantization of slightly different models, in which the fundamental constants undergo cyclic evolution [26], yields insight into the relationship between quantum entanglement and thermodynamics [27].…”
Section: Introductionmentioning
confidence: 67%
“…Within the concept of the multiverse, there is a growing approach that regards the minisuperspace as the fundamental arena for physical phenomena to take place [22,25,28,29,31,32,33,34,35,36,37,38]. Particular models include different types of interactions between the wave functions that represent individual universes [25,31,34,35,36,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations